Design of a Versatile and Low Cost μVolt Level A to D Conversion System for Use in Medical Instrumentation Applications. (23rd September 2008) - Williams Williams, Kerry Kerry; Robinson Robinson, Neil Neil
Abstract : Modern medical facilities place considerable reliance on electronic instrumentation for purposes of calibration and monitoring of therapeutic processes, many of which employ electrical and electronic apparatus that itself generates considerable levels of interference in the form of background electromagnetic radiation (EMR). Additionally diverse ambient conditions in the clinical environment such as uncontrolled temperature, humidity, noise, and vibration place added stress on sensitive instrumentation. In order to obtain accurate, repeatable, and reliable data in such environments, instrumentation used must be largely immune to these factors. Analogue instrumentation is particularly susceptible to unstable environmental conditions. Sensors typically output an analogue current or voltage and it can be demonstrated that considerable overall benefit to the measuring process would result if sensor outputs could be converted to a robust digital format at the earliest possible stage. A practical and low cost system for A to D conversion atμ Volt signal levels is described in this work. It has been successfully employed in portable radiation dosimetry instrumentation and used under diverse clinical conditions and it affords an improvement in signal resolution in excess of an order of magnitude over commonly used analogue techniques.